Epilepsy with cognitive deficit and autism spectrum disorders: Prospective diagnosis by array CGH123. Issue 1 (26th November 2012) - Nicholl, Jillian; Waters, Wendy; Suwalski, Shanna; Brown, Sue; Hull, Yvonne; Harbord, Michael G.; Entwistle, John; Thompson, Suzanna; Clark, Damian; Pridmore, Claire; Haan, Eric; Barnett, Christopher; et al.
Abstract The clinical significance of chromosomal microdeletions and microduplications was predicted based on their gene content, de novo or familial inheritance and accumulated knowledge recorded on public databases. A patient group comprised of 247 cases with epilepsy and its common co‐morbidities of developmental delay, intellectual disability, autism spectrum disorders, and congenital abnormalities was reviewed prospectively in a diagnostic setting using a standardized oligo‐array CGH platform. Seventy‐three (29.6%) had copy number variations (CNVs) and of these 73 cases, 27 (37.0%) had CNVs that were likely causative. These 27 cases comprised 10.9% of the 247 cases reviewed. The range of pathogenic CNVs associated with seizures was consistent with the existence of many genetic determinants for epilepsy. © 2012 Wiley Periodicals, Inc.